La entonación en hablantes lojanos - Orellana Vásquez, Danny Alexander (2022)
The objective of this research is to analyze intonation in speakers from Loja. Theoretically, the research is based on Alarcos Llorach (1981), Quilis (1996), RAE (2010) and Hualde (2014), who define intonation and explain its function. The Praat program was used to carry out the analysis process. As informants, four speakers from the Loja canton were selected, two male and two female, who make up the corpus currently being built by the National University of Loja. A total of 36 statements were processed, 9 for each informant. They are distributed in 3 assertive sentences, 3 interrogative and 3 exclamatory. The most relevant results indicate that, as usually happens in any speaker of any language, the intonation in Lojano is reflected through the melodic curve. Also, that changes in intonation depend on melodic patterns, intensity, tone and frequencies. In addition, they show that female informants have a higher tone than male informants in assertive and exclamatory sentences. And a single male informant from the third generation presented a neutral tonality in all three types of sentences. On the other hand, it was found that monotonal and bitonal accents are used in the three types of sentences with variations ranging from L+H*, H+L*, H>L+H* and vice versa with minimum frequencies of 51.25 dB and 81.51Hz. .